Solar heating and cooling systems fundamentals, experiments and applications - Sarbu, Ioan; Sebarchievici, Calin (Amsterdam Academic Press, 2017)
Solar Heating and Cooling Systems: Fundamentals, Experiments and Applications provides comprehensive coverage of this modern energy issue from both a scientific and technical level that is based on original research and the synthesis of consistent bibliographic material that meets the increasing need for modernization and greater energy efficiency to significantly reduce CO2 emissions. Ioan Sarbu and Calin Sebarchievici present a comprehensive overview of all major solar energy technologies, along with the fundamentals, experiments, and applications of solar heating and cooling systems. Technical, economic, and energy saving aspects related to design, modeling, and operation of these systems are also explored. This reference includes physical and mathematical concepts developed to make this publication a self-contained and up-to-date source of information for engineers, researchers, and professionals who are interested in the use of solar energy as an alternative energy source.--Provided by publisher.
Introduction -- Solar radiation -- Solar collectors -- Thermal energy storage -- Solar water and space-heating systems -- Head distribution systems in buildings -- Solar thermal-driven cooling systems -- Solar electric cooling systems -- Solar-assisted heat pumps.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Solar heating; Solar heating -- Equipment and supplies; Solar air conditioning; Electronic books